Linking with light [high-speed optical interconnects]. - Savage, N. (IEEE spectrum)
Having proven their worth in long-distance communications, photons will soon take over inside the computer. So some researchers say that, within just a few years, many of the copper connections in computers will yield to high-speed optical interconnects, in which photons, rather than electrons, will pass signals from board to board, or chip to chip, or even from one part of a chip to another. The idea is simple in principle, and parallels telecommunications systems. An electrical signal from the processor would modulate a miniature laser beam, which would shine through the air or a waveguide to a photodetector, which would in turn pass the signal on to the electronics. Though at the moment it is more expensive to communicate with light than with electric current, the day is coming when only optical technologies will be able to keep up with the demands of ever-more-powerful microprocessors, just as they are now the only reasonable way to move the world's Internet traffic across the kilometers.